The Effect of Business Strategy on Company Performance with a Management Control System as a Moderation Variable - Retno Febriani Pratomowati; Elok Savitri Pusparini (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the suitability of business strategies based on the Miles & Snow typology and the type of Management Control System (MCS) on company performance, with Return on Assets (ROA) as the main indicator, using a sample of 82 non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2014 to 2023. This study uses a quantitative approach with longitudinal data, applying cluster analysis, ANOVA, and Games-Howell post hoc test to analyze the suitability between business strategies (defenders, prospectors, analyzers) and MCS types (clan, adhocracy, market, hierarchy). The findings of the study show that the alignment between the business strategy and the type of MCS has a significant effect on the financial performance of the company. The defender strategy gains higher ROA when supported by market-oriented MCS, while the prospector strategy performs best with a clan or adhocracy-type MCS that emphasizes flexibility and innovation. The analyzer strategy has proven to consistently produce stable performance on all types of MCS, confirming its adaptive character. This study highlights the importance of regular evaluation of the suitability of the MCS-strategy and the role of Top Management Team (TMT) characteristics in supporting effective implementation. The results of this study provide theoretical reinforcement for contingency theory and strategic fit, as well as practical guidance for managers to design a Management Control System (MCS) that improves the company's competitiveness and resilience in a dynamic business environment.